Review Article: Travel Medicine Residency Training in Thailand and Foreign Countries - วงศ์สุธีรา, จุฑามาศ; เหล่าลือเกียรติ, ธิดาพร; ชูเชิด, สาธิณี; ศุภณัฐเศรษฐกุล, ณตพล (Journal of Preventive Medicine Association of Thailand, 2018)
Travel-related health problems can be occurred in both the travelers themselves and the general population introduced by a traveler. Preventive medicine, especially travel medicine, is dealing with not only taking care of the travelers’ health throughout the journey, but also acting on the disease surveillance and prevention from a spreadable disease associated with travelers. The first recognized residency training program in preventive medicine (travel medicine) has been operated in Thailand since 2014. This 3-year residency training program includes preventive/travel medicine training, clinical tropical medicine training and research training, under the supervision by Preventive Medicine Association of Thailand and The Medical Council of Thailand. Currently, there are 2 main residency training institutes, consisting of the Faculty of Tropical Medicine, Mahidol University and the Institute of Preventive Medicine, Department of Disease Control, Ministry of Public Health. There are 5 training positions per institute available each year. Two candidates have been successfully graduated in the first batch from the Faculty of Tropical Medicine, Mahidol University last year. In foreign countries, there are several training programs in travel medicine. Most of them are short courses, and the applicants can be doctor, nurse, or other medical personnel practicing in travel medicine. An examination for the internationally recognized certificate of knowledge in travel medicine is available by International Society of Travel Medicine (ISTM). Useful information and websites are also included in this article for medical students, doctors, and others who interest further study in travel medicine.